Research on microstructure evolution and mechanical properties of steering shaft teeth after pre-heat treatment and carburizing-quenching processes. Issue 1 (July 2021) - Zhang, Yishuai; Wang, Tao; Fu, Jia; Sun, Hongxing; Li, Jiqiang; Liu, Hua
Abstract: The influence of pre-heat treatment and carburizing quenching on microstructure and properties in steering gear is studied. The CCT curve and TTT curve of 20CrMnTiH are calculated by JMatPro software. According to the phase transformation theory of undercooled austenite, the pre-heat treatment process is designed and the carburizing and quenching experiments are carried out in a gas carburizing furnace. Results show that the undercooled austenite begins to transform at 814.1 °C and shows unstable at 650 °C, at which the phase transformation speed is the fastest; By controlling the cooling rate of our designed air cooling system, transformation temperature and transformation time during the undercooled austenite transformation, the metallographic structure of axle teeth after pre-heat treatment can reach grade 1, with the brinell hardness distribution is 159HB-166HB and the hardness difference less than 7HB. After carburizing and quenching the carbide grade in the gear surface can reach to grade 1. The acicular martensite and retained austenite can also reach to grade 3. In the surface of the gear the hardness is 704HV. With the request of the engineering technical standard of 0.7mm-0.9mm, the effective hardened layer depth is about 0.85 mm. This research provides a technical basis for the fatherly research on distortion characteristics.